On the Measurement and Control of Beta Change: Reply to Terborg, Maxwell, and Howard - Armenakis, Achilles A.; Bedeian, Arthur G. (Academy of Management Review, 1982)
Achilles A. Armenakis, Arthur G. Bedeian, On the Measurement and Control of Beta Change: Reply to Terborg, Maxwell, and Howard, The Academy of Management Review, Vol. 7, No. 2 (Apr., 1982), pp. 296-299